Impacto da oxidação química por persulfato em solo tropical: avaliação em sistemas de transporte 1-D - Favero, Mariana [UNIFESP] (2017)
Recently in situ chemical oxidation (ISCO) has been a remedy of choice for sites contaminated with organic compounds. However, the impact of the chemical oxidant on soil properties and, therefore, on solute transport and remediation efficiency still lacks understanding. Thus, this work sought to evaluate the changes in soil physical properties of an Oxisol resulting from potassium persulfate oxidation. One-dimensional laboratory experiments were performed using saturated undisturbed columns. The injection of persulfate was carried out in two Oxisol columns and two another columns were used as acid and water controls, respectively. Transport parameters (longitudinal dispersity and retardation factor) and the effective porosity were obtained by fitting the breakthrough curves with an analytical solution for one-dimensional transport. During oxidation, hydraulic conductivity was monitored and pH, Eh, persulfate concentration, Al (III), Fe (II) and total iron concentration were measured. Phenol was chosen as a reactive tracer and had its retardation and decay determined before and after oxidation. Micromorphological analyses were conducted on impregnated soil blocks from control and oxidized systems as a tool of soil structure changes determination. Effective porosity did not show a significant variation after oxidation for both soil columns. Hydraulic conductivity increased on both soil columns during the first 100 h of persulfate injection. Concurrent with the breakthrough of persulfate, the pH decreased (until 3,0-3,5) and a progressive release of Al (III) was observed. Sulfuric acid injection resulted in Al (III) release eight times higher than that in oxidized columns. Water injection decreased hydraulic conductivity about one order of magnitude. Phenol mass was adsorbed in all undisturbed columns, probably due to phenol interaction with coal in Oxisol. Micromorphological analysis showed that persulfate produced alterations in poroids types distribution, which affects soil permeability and solute dispersivity. It was verified that persulfate promotes significant changes in Oxisol physical properties, which can result in transport alterations of solutes, as contaminants or remediation solutions.